Benchmarking of Bat-inspired Interaction Testing Strategy - Kamal Z., Zamli; Alsariera, Yazan A.; Nasser, Abdullah B. (International Science Press (Serials Publications Pvt. Ltd.), 2016)
Although desirable, exhaustive testing of the software system is impractical because of the significant growth of the search space of systems features (large search space).Several sampling strategies have been introduced to systematically reduce the test data for consideration. Complementing existing sampling strategies (i.e. in terms of dealing with interaction faults). To be specific, the interaction testing technique (refers to as t-way strategy) is based on interaction strength and is capable of dramatically reducing the number of test suite while ensuring practical coverage. T-way interaction testing has been extensively exploited resulting into many prototypes strategy implementations. Recently, there are growing interests for adopting optimization algorithms as the basis of the newly developed strategies contributing to the new and upcoming search based software testing (SBST) area of research. In this article, we benchmarked the bat-inspired testing strategy (BTS) for uniform strength interaction against some of the available t-way testing tools and strategies. Based on the benchmarking results, BTS achieved some new minimum test suite sizes over the existing strategies.